Instance cloned extreme learning machine. (August 2017) - Zhang, Yongshan; Wu, Jia; Zhou, Chuan; Cai, Zhihua
Highlights: Instance cloning technique is used for improving Extreme Learning Machine. The proposed method is an effective local learning method for classification problems. We analyze the sensitivity of two key parameters in the proposed method. Experimental results on a large number of datasets demonstrate the algorithm performance. Abstract: Extreme Learning Machine (ELM) is a popular machine learning method which can flexibly simulate the relationships of real-world classification applications. When facing problems ( i.e., data sets) with a smaller number of samples ( i.e., instances), ELM may often result in the overfitting trouble. In this paper, we propose a new Instance Cloned Extreme Learning Machine (IC-ELM for short) which can handle numerous different classification problems. IC-ELM uses an instance cloning method to balance the input data's distribution and extend the training data set, which alleviates the overfitting issue and enhances the testing classification accuracy. Experiments and comparisons on 20 UCI data sets, and validations on image and text classification applications, demonstrate that IC-ELM is able to achieve superior results compared to the original ELM algorithm and its variants, as well as several other classical machine learning algorithms.